Topical issues of improving Ukrainian legislation regulating the prevention and counteraction to smuggling and certain legal elements of customs rules’ violation - V. T. Komziuk; A. A. Komziuk (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The authors of the article analyze the measures for preventing and counteracting smuggling defined in the Customs Code of Ukraine and other acts of customs legislation, the imperfection of the normative consolidation of such measures in the Customs Code and the problematic issues of their implementation. The most important measures aimed at counteracting smuggling were suggested, which were defined by normative acts of the Cabinet of Ministers and the President of Ukraine, and were offered to strengthen them in legislation, in Section 17 of the Customs Code, which determined (though depleted) measures to prevent and counteract to smuggling. In particular, the expediency of introducing amendments to the Art. 456 of the Customs Code of Ukraine is substantiated, which would generally define the procedure for the controlled delivery of drugs, psychotropic substances and precursors, which should be detailed in the relevant normative act that should be promptly adopted by the competent authorities. It is also suggested to amend the Art. 456 of the Customs Code of Ukraine, which does not correctly define the objects of smuggling, which are subject to prevention and counteraction with regard to their illegal trafficking across the customs border of Ukraine.